Identification of the High Mannose N‑Glycan Isomers Undescribed by Conventional Multicellular Eukaryotic Biosynthetic Pathways - Liew, Chia Yen; Luo, Hong-Sheng; Yang, Ting-Yi; Hung, An-Ti; Magoling, Bryan John Abel; Lai, Charles Pin-Kuang; Ni, Chi-Kung (Analytical chemistry (Washington), 2023)
N-linked glycosylation is one of the most important post-translational modifications of proteins. Current knowledge of multicellular eukaryote N-glycan biosynthesis suggests high mannose N-glycans are generated in the endoplasmic reticulum and Golgi apparatus through conserved biosynthetic pathways. According to conventional biosynthetic pathways, four Man7GlcNAc2 isomers, three Man6GlcNAc2 isomers, and one Man5GlcNAc2 isomer are generated during this process. In this study, we applied our latest mass spectrometry method, logically derived sequence tandem mass spectrometry (LODES/MS n ), to re-examine high mannose N-glycans extracted from various multicellular eukaryotes which are not glycosylation mutants. LODES/MS n identified many high mannose N-glycan isomers previously unreported in plantae, animalia, cancer cells, and fungi. A database consisting of retention time and CID MS n mass spectra was constructed for all possible Man n GlcNAc2 (n = 5, 6, 7) isomers that include the isomers by removing arbitrary numbers and positions of mannose from canonical N-glycan, Man9GlcNAc2. Many N-glycans in this database are not found in current N-glycan mass spectrum libraries. The database is useful for rapid high mannose N-glycan isomeric identification.